Pengaruh Anggaran Berbasis Kinerja Terhadap Akuntabilitas Kinerja Instansi Pemerintah (Studi Kasus Pada RSUD Sidoarjo) - Marselia, Irene Thia; Ardhiarisca, Oryza (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2023)
The purpose of this research was to examine the effect of planning, implementing, reporting, and evaluating performance which is a performance-based budgeting cycle to performance accountability. This type of research is causal research using a quantitative approach. The population of this study is the employees of the finance department at Sidoarjo Hospital. In determining the sample, the determination of the saturated sample was used so that the entire population in this study became the research sample. This study uses primary data by giving questionnaires to research respondents. Data analysis in this study used multiple linear regression analysis, simultaneous and partial tests. The results of this study indicate that the four variables have a significant effect on the performance accountability of government agencies.